Trio op. 9 de Henrique Oswald: uma edição crítica - Helcio Vaz do Val (2012)
Henrique Oswald (1852-1931) was a musician of notable acting in brazilian music scene. His output is extensive and diverse, and comprises practically every musical genre. Nevertheless, for many years his works were neglected in favor of nationalist music, and much of his work isnt yet published, existing only in manuscripts. In recent years, studies about his life and works, as well as editions of his music are multiplying, and his output is coming back to light. In the present work, we accomplished a critical edition of his Trio op. 9 for violin, cello and piano, an important work in the composers output and not yet edited. The edition was made in the software Finale based on four manuscripts, three being complete and one incomplete. The manuscript copy preserved in Arquivo Nacional (RJ) was taken as main source, since it presents important and functional alterations concerning performance, and information from the other sources were also used. The manuscripts were compared and the differences between them were listed and divided into categories for easier viewing and facilitation of choices, and the choices and editorial interventions were justified. The edited score and the separate violin and cello parts are included in the work.